DETERMINAN KEPATUHAN WAJIB PAJAK HOTEL - I Nyoman Wijana Asmara Putra; Anak Agung Gde Putu Widanaputra; I Putu Bayu Suyadnya Pratama; Ni Luh Tillatama Sidhirastu (Faculty of Economics and Business, Universitas Warmadewa, 2026)
The government has issued various policies to raise taxpayer compliance, yet studies on regional taxes—such as hotel tax—remain limited. Hotel tax is collected by third parties (hotels) from customers, and this delegated authority can be misused for internal interests. This study examines factors influencing hotel taxpayers’ compliance intentions using the Theory of Planned Behavior. The population comprises 2,642 hotel taxpayers in Denpasar, Badung, Gianyar, and Tabanan. A sample of 100 was drawn via probability sampling using the Slovin formula. Data were gathered through 5-point Likert questionnaires distributed both offline and online. The instrument underwent validity and reliability testing, and responses were analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results show that tax morale, taxpayer awareness, tax fairness, trust in government, the power of tax authorities, tax convenience, and tax information positively affect compliance intentions. In other words, higher tax morale and awareness, stronger perceptions of fairness, greater trust in government, stronger perceived authority, easier procedures, and better information are associated with higher intentions among hotel businesses to comply with hotel tax.